The Possible Clinical Predictors of Fatigue in Parkinson’s Disease: A Study of 135 Patients as Part of International Nonmotor Scale Validation Project - Barone, P.; Stocchi, Fabrizio; Antonini, Angelo; Chaudhuri, K. Ray; Martin, Anne; Kaluarachchi, T. K.; Schartau, P. E. S.; Gage, Heather M.; Martinez-Martin, Pablo; Logishetty, Kartik; Metta, Vinod; Odin, Per (Parkinson's disease, 2011)
Fatigue is a common yet poorly understood and underresearched nonmotor symptom in Parkinson's disease. Although fatigue is recognized to significantly affect health-related quality of life, it remains underrecognised and empirically treated. In this paper, the prevalence of fatigue as measured by a validated visual analogue scale and the Parkinson's disease nonmotor symptoms scale (PDNMSS) was correlated with other motor and nonmotor comorbidities. In a cohort of patients from a range of disease stages, occurrence of fatigue correlated closely with more advanced Parkinson's disease, as well as with depression, anxiety, and sleep disorders, hinting at a common underlying basis.